Increased α2-6 sialylation of endometrial cells contributes to the development of endometriosis - Choi, Hee-Jin; Chung, Tae-Wook; Choi, Hee-Jung; Han, Jung Ho; Choi, Jung-Hye; Kim, Cheorl-Ho; Ha, Ki-Tae (Experimental & molecular medicine, 2018)
Endometriosis is a disease characterized by implants of endometrial tissue outside the uterine cavity and is strongly associated with infertility. Focal adhesion of endometrial tissue to the peritoneum is an indication of incipient endometriosis. In this study, we examined the effect of various cytokines that are known to be involved in the pathology of endometriosis on endometrial cell adhesion. Among the investigated cytokines, transforming growth factor-β1 (TGF-β1) increased adhesion of endometrial cells to the mesothelium through induction of α2-6 sialylation. The expression levels of β-galactoside α2-6 sialyltransferase (ST6Gal) 1 and ST6Gal2 were increased through activation of TGF-βRI/SMAD2/3 signaling in endometrial cells. In addition, we discovered that terminal sialic acid glycan epitopes of endometrial cells engage with sialic acid-binding immunoglobulin-like lectin-9 expressed on mesothelial cell surfaces. Interestingly, in an in vivo mouse endometriosis model, inhibition of endogenous sialic acid binding by a NeuAcα2-6Galβ1-4GlcNAc injection diminished TGF-β1-induced formation of endometriosis lesions. Based on these results, we suggest that increased sialylation of endometrial cells by TGF-β1 promotes the attachment of endometrium to the peritoneum, encouraging endometriosis outbreaks. Endometriosis: a sweet and sticky mechanism uncovered A growth factor involved in cell differentiation and proliferation contributes to the development of endometriosis by stimulating a protein modification mechanism that increases the adhesiveness of cells lining the uterus. Endometriosis results when these cells, known as endometrial cells, start growing outside the uterus causing pelvic pain, heavy periods and, in some cases, infertility. Ki-Tae Ha at Pusan National University, Yangsan, South Korea, and colleagues found that transforming growth factor-β1 signaling promoted the addition of sialic acid sugar units onto endometrial cell surface proteins. This modification enhanced the adhesion of endometrial cells to mesothelial cells, which line other internal organs, and the formation of endometriosis lesions in mice. Preventing sialic acid binding to its mesothelial cell receptor reduced lesion formation. The findings reveal a new molecular mechanism underlying endometriosis and a potential treatment strategy.